Comparison Analysis Between Traditional and Long Segment Contracts on National Road Preservation Activities in Indonesia - Winanri, R. P.; Susanti, B.; Juliantina, I. (Engineering, Technology & Applied Science Research, 2019)
National road preservation activities in Indonesia are usually carried out using a traditional approach system, namely in-house system and contract system with a design-bid-build (DBB) approach. An alternative contract method to improve the quality of roads is the long segment contract. Its definition is carrying out road preservation activities in one continuous segment with the aim to obtain good road conditions for all segments. This study aims to compare the performance under traditional approaches and long segment contracts. Road performance is expressed in functional performance terminology and uses the International roughness index (IRI) indicator. The research was conducted on the outer urban road of Palembang - Indralaya intersection - Meranjat which is part of the national road section in the Province of South Sumatra, Indonesia. Results showed that the road performance contracted with traditional approaches was better than that of long segment ones. This was not expected and was probably due to the lack of understanding of the parties involved in the long segment contract to the principles of fulfilling road service performance. The contractors are not interested in carrying out routine road maintenance projects because the value of the work is small and there is a lack of experience regarding routine maintenance.